Electrocardiographic findings and prognosis in ischemic stroke - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2003)
Introduction: Electrocardiographic (ECG) changes are observed in patients with acute stroke and are related with the prognosis. Aims: To determine the frequency and significance of ECG changes in patients with acute ischemic stroke. Material and Methods: In a prospective hospital-based study 87 patients with cerebral infarction were observed for ECG changes during their stay in the hospital. All the patients had ischemic stroke for the first time. The ECG changes observed were compared with those of the control group consisting of 87 patients. Results: Of the 87 patients of the study group, 47.1% were females and 52.9% males. The mean age was 65.5+/-11.9. (range 31-91 yrs). The control group consisted of 50.6% females and 49.4% males. The mean age was 64.5+/-9.1 (range 31-87 yrs). The frequency of the ECG changes observed in patients with cerebral infarct was 62.1% while it was 29.9% in the control group (P<0.0001). ECG changes observed were mostly related to myocardial ischemia. The six-month mortality rate in the patients with ECG changes was 38.9% whereas it was 15.2% in those with normal ECG (P<0.05). Conclusions: The observations of this study suggest that cardiac evaluation in patients with acute ischemic stroke is of prognostic importance.
Keywords: ischemic stroke; electrocardiography; prognosis